2001
DOI: 10.1046/j.0306-5251.2001.01469.x
|View full text |Cite
|
Sign up to set email alerts
|

Herb–drug interactions: Review and assessment of report reliability

Abstract: Aims The aim of this systematic review was to assess the published clinical evidence on interactions between herbal and conventional drugs. Methods Four electronic databases were searched for case reports, case series or clinical trials of such interactions. The data were extracted and validated using a scoring system for interaction probability. Results One hundred and eight cases of suspected interactions were found. 68.5% were classi®ed as`unable to be evaluated', 13% as`well-documented' and 18.5% as possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
207
0
8

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 317 publications
(215 citation statements)
references
References 54 publications
0
207
0
8
Order By: Relevance
“…Systematic reviews were carried out recently to assess the published clinical evidence on interactions between herbal and conventional drugs. 26,27 As a result, many cases of suspected interactions were found. It was reported that warfarin was the most common drug and St. John's wort (Hypericum perforatum) was the most common herb involved.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic reviews were carried out recently to assess the published clinical evidence on interactions between herbal and conventional drugs. 26,27 As a result, many cases of suspected interactions were found. It was reported that warfarin was the most common drug and St. John's wort (Hypericum perforatum) was the most common herb involved.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of 44 of the leading dietary supplement manufacturers in 2003 revealed that only 10 of 15 respondents considered interactions to be an important issue, and only 2 allocated funds to study herbal-drug interactions (39). Poor reliability of the It was reported in a study that of one hundred and eight cases of suspected interactions studied, 68.5% were classified as 'unable to be evaluated', 13% as 'well-documented' and 18.5% as 'possible' interactions (40). One of the major reasons for this unreliability of reports of the clinical evidence on interactions between herbal and conventional drugs is the inherent scientific and clinical challenges in the use of herbal medicines.…”
Section: Challenges To Botanical-drug Interactions Researchmentioning
confidence: 99%
“…Interactions with other drugs during external use are not full-understood due to small and short systemic absorption. However, there is a case of 53-year-old female patient receiving angiotensin converting enzyme inhibitor (ACEI) with recurrent cough appearing only after application of topical capsaicin 0.075% cream which suggests that capsaicin may cause or exacerbate ACE inhibitor-induced cough [89].…”
Section: Contraindications Interactions With Other Drugsmentioning
confidence: 99%